A 'HEART OF GOAL' AND THE WILL TO SUCCEED: GOAL COMMITMENT AND TASK PERFORMANCE AMONG TEACHERS IN PUBLIC SCHOOLS. (24th July 2015) - PEDERSEN, MOGENS JIN
Abstract : Much research suggests that employee goal commitment is predictive of work behaviour and performance. However, public administration research has yet to establish the linkage between goal commitment and task performance in the context of public service employees. Using survey data on school teachers with administrative data on students, this article employs within‐student between‐teachers fixed effects and shows how teachers' goal commitment affects their task performance. Moreover, the article shows how task difficulty moderates this relationship. The findings suggest that higher goal commitment promotes teacher task performance, in particular, at moderate to high levels of task difficulty.